Geospatial information for African agriculture: a key investment for agricultural policies - Tonneau, Jean-Philippe; Bégué, Agnès; Leroux, Louise; Augusseau, Xavier; Faure, Jean-François; Mertens, Benoit; Pinet, Camille; Tomasini, Linda (Perspective, 2019)
Version française de l'article Geospatial information and its derived products, designed to contribute to public agricultural policy making, are not widely used in Africa. The infrastructure, training and skills are lacking, and research and development activities are dispersed and inadequate. More importantly, needs are not formalised and technological resources, driven by the industrialised countries, are ill-adapted to the characteristics of agricultural systems in Africa. Moreover, companies, institutions and projects require a stable environment to ensure operational services, relevant products and useful information. These co-constructed services emerge within long-term partnerships between researchers, consultancies and end users. Research thus offers new opportunities for using satellite imagery to document and explain agricultural transformation processes. Finally, lasting interdisciplinary skills networks are needed to facilitate methodological and thematic exchanges.